The dynamics of mature and emerging freshwater conservation programs - Neeson, Thomas M.; Wineland, Sean M.; Phillips, Erin; McFadden, Jonathan (Frontiers in Environmental Science, 2022)
Conservation programs range from small, place-based initiatives to large, bureaucracy-heavy systems. The dynamics of these programs vary greatly. New initiatives may experience exponential growth, but participation and spending in mature programs may rise and fall in response to a number of factors. Here, we analyze historical patterns of participation and spending across five freshwater conservation programs in the United States. Our analysis highlights fundamental differences between emerging programs, which may experience exponential or logistic growth, and mature programs with slower growth, in which changes in participation may be driven by a number of internal and exogenous factors. We propose that changes in the number and spatial distribution of conservation projects are associated with four key factors: changes in legislation that open new funding streams; shifting priorities of actors; changes in the policies or management of a program that align it with new funding streams; and increases in individuals’ willingness to participate in a program as it grows. These programmatic shifts represent windows of opportunity for strategically reorienting conservation programs to leverage newly-available resources. Given that large, mature conservation programs support biodiversity and ecosystem services worldwide, comparison of their dynamics with those of emerging programs may reveal key opportunities for maximizing the benefits of investments in these programs.